Kurikulum TVET Adaptif Berbasis Data : Tinjauan Sistematis atas Model Penyesuaian Dinamis terhadap Kebutuhan Industri - Handepi, Nogi; Maiharni, Yetti; Refdinal; Abdullah, Rijal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article systematically reviews how Technical and Vocational Education and Training (TVET) curricula can be dynamically adjusted through industry-demand data, labor market intelligence, and stakeholder feedback mechanisms. The review was prepared from the provided article outline, the PRISMA 2020 flow material, and a Scopus export containing an initial corpus of 516 records and seven studies included in the qualitative synthesis. The analysis focuses on four themes: data-driven curriculum models, the role of Labor Market Information Systems (LMIS), TVET–industry collaboration mechanisms, and dynamic curriculum adjustment models. The synthesis shows that adaptive TVET curricula are being shaped through three major pathways: job-vacancy analytics, indicator-based and statistical curriculum optimization, and stakeholder-driven curriculum reconstruction. Available evidence suggests that these approaches improve the relevance of learning outcomes, update module priorities, and strengthen the alignment between practical learning and actual workplace requirements. At the same time, the literature reveals persistent limitations, including uneven data integration, the dominance of conceptual or simulation-based evidence, and the lack of longitudinal employability evaluation. This review argues that TVET reform should move beyond conventional outcome-based education and be redesigned as an adaptive system connecting labor market data, agile curriculum governance, and intensive industry collaboration.